2021
DOI: 10.1186/s12871-021-01348-z
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of preoperative dexamethasone administration on cognitive function after cardiac surgery: a 4-year follow‐up of a randomized controlled trial

Abstract: Background The pathogenesis of postoperative cognitive decline (POCD) is still poorly understood; however, the inflammatory response to surgical procedures seems likely to be involved. In addition, our recent randomized controlled trial showed that perioperative corticosteroid treatment may ameliorate early POCD after cardiac surgery. To assess the long-term effect of dexamethasone administration on cognitive function, we conducted a 4-year follow-up. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 31 publications
1
22
0
3
Order By: Relevance
“…While preoperative administration of dexamethasone showed some benefit in reducing POD at the 6 day and 4-year mark, it did not reach statistical significance. 6 In another review covering over 8000 patients it was determined that while administration of glucocorticoids did not reduce POD, they did reduce time on the ventilator, as well as time in the ICU--two factors that we know greatly contribute to the development of POD. 7 The meta-analysis did not show any significant impact on blood sugar, wound healing or gastric injury in the trial group compared to the control group--possibly indicating that the administration of steroids may provide some benefit without a significant detrimental effect.…”
Section: Steroidsmentioning
confidence: 99%
“…While preoperative administration of dexamethasone showed some benefit in reducing POD at the 6 day and 4-year mark, it did not reach statistical significance. 6 In another review covering over 8000 patients it was determined that while administration of glucocorticoids did not reduce POD, they did reduce time on the ventilator, as well as time in the ICU--two factors that we know greatly contribute to the development of POD. 7 The meta-analysis did not show any significant impact on blood sugar, wound healing or gastric injury in the trial group compared to the control group--possibly indicating that the administration of steroids may provide some benefit without a significant detrimental effect.…”
Section: Steroidsmentioning
confidence: 99%
“…The use of drug during anesthesia process also significantly affects the development of POCD. Glumac et al also found that the prophylactic administration of dexamethasone seems to be useful to prevent POCD development following cardiac surgery [ 30 ]. Insomnia will lead to increased aldosterone secretion in the body and increased blood pressure [ 23 , 24 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…That was also the first study to confirm that the systemic inflammatory response is inhibited by dexamethasone based on inflammatory markers ( p < 0.001). In a follow-up from their 2017 study, Glumac et al ( 83 ) observed that dexamethasone reduced the incidence of cognitive impairment over 4 years. However, this finding narrowly failed to reach significance (RR: 0.459; 95% CI: 0.192–1.100; p = 0.068) ( 83 ).…”
Section: Pathophysiology Of Postoperative Cognitive Dysfunction Follo...mentioning
confidence: 98%
“…In a follow-up from their 2017 study, Glumac et al ( 83 ) observed that dexamethasone reduced the incidence of cognitive impairment over 4 years. However, this finding narrowly failed to reach significance (RR: 0.459; 95% CI: 0.192–1.100; p = 0.068) ( 83 ). This study was the first long-term study to assess the effect of dexamethasone on cognitive outcomes following cardiac surgery.…”
Section: Pathophysiology Of Postoperative Cognitive Dysfunction Follo...mentioning
confidence: 98%
See 1 more Smart Citation